In Vivo Processing of Ceria Nanoparticles inside Liver: Impact on Free‐Radical Scavenging Activity and Oxidative Stress. Issue 8 (6th June 2014) - Graham, Uschi M.; Tseng, Michael T.; Jasinski, Jacek B.; Yokel, Robert A.; Unrine, Jason M.; Davis, Burtron H.; Dozier, Alan K.; Hardas, Sarita S.; Sultana, Rukhsana; Grulke, Eric A.; Butterfield, D. Allan
Abstract The cytotoxicity of ceria ultimately lies in its electronic structure, which is defined by the crystal structure, composition, and size. Despite previous studies focused on ceria uptake, distribution, biopersistance, and cellular effects, little is known about its chemical and structural stability and solubility once sequestered inside the liver. Mechanisms will be presented that elucidate the in vivo transformation in the liver. In vivo processed ceria reveals a particle‐size effect towards the formation of ultrafines, which represent a second generation of ceria. A measurable change in the valence reduction of the second‐generation ceria can be linked to an increased free‐radical scavenging potential. The in vivo processing of the ceria nanoparticles in the liver occurs in temporal relation to the brain cellular and protein clearance responses that stem from the ceria uptake. This information is critical to establish a possible link between cellular processes and the observed in vivo transformation of ceria. The temporal linkage between the reversal of the pro‐oxidant effect (brain) and ceria transformation (liver) suggests a cause–effect relationship.